Comparison Of Sanctions For The Crime Of Adultery In Toraja Customary Law And National Law In Indonesia - Sugeng Muntaha; Ade Saptomo (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
This research aims to analyze the comparison of sanctions for the crime of adultery in the context of Toraja customary law and national law in Indonesia. Adultery is a violation of social norms that has legal implications, but handling can differ between customary law and national law. The research method used is a descriptive-analytical approach by collecting data from primary and secondary sources. The research results show that in Toraja customary law, sanctions for the crime of adultery tend to be restorative in nature and involve customary deliberation to achieve reconciliation between the parties concerned. On the other hand, national law in Indonesia regulates sanctions for the crime of adultery through criminal law instruments with the potential for a prison sentence. This comparison provides an in-depth understanding of the differences in approaches between customary law and national law in dealing with the crime of adultery. The implications include the need for harmonization or synchronization between customary law and national law to ensure justice and sustainability of legal norms in society. This research can be the basis for improving legal regulations that are more inclusive and in line with local values and community needs.